Association of Dietary Energy Intake With Constipation Among Men and Women: Results From the National Health and Nutrition Examination Survey - Yang, Shuai; Wu, Xiao-Li; Wang, Shou-Qing; Guo, Xiang-Ling; Guo, Fu-Zheng; Sun, Xiao-Feng (Frontiers in Nutrition, 2022)
Abstract Background: Previous studies support that dietary factor is associated with constipation; the relationship between dietary energy intake and constipation has not been well studied. We aim to evaluate the prevalence and correlation between energy intake and constipation among men and women. Methods: These observational analyses included 12587 adults (≥20 years) from the 2005-2010 cycles of the National Health and Nutrition Examination Surveys (NHANES). Constipation was defined as Bristol Stool Scale Type 1(separate hard lumps, like nuts) or Type 2(sausage-like but lumpy). Energy intake was obtained from the two 24-hour dietary recalls and averaged. We used the logistic regression model in Generalized Linear Model (GLM) function, controlling demographic, lifestyle, and dietary factors, to estimate the association between energy intake and constipation among males and females. Results: the overall incidence of constipation in this research was 8.1%, the incidence in women and men was 11.2% and 5.1%, respectively. After multivariable adjustment, middle energy consumption correlated with decreased risk of constipation in men (OR:0.50, 95%CI:0.29-0.85), lower-middle energy intake increased the constipation risk in women (OR:1.55, 95%CI:1.14-2.10). High energy consumption was not associated with increased or decreased constipation risk. Conclusions: To our knowledge, this is the first research to investigate the association between energy intake and constipation; the study demonstrates that appropriate energy consumption can help reduce the risk of constipation in men, and relatively low energy intake is associated with increased constipation risk in women.